FACTORS FOR URINARY INCONTINENCE IN FEMALES PRESENTING IN TERTIARY CARE HOSPITAL - Mudassar Saeed Pansota; Anum Iftikhar; Arslan Ahmed; Iftikhar Ahmad; Haﬁz Muhammad Tariq; Muhammad Shahzad Saleem (Journal of University Medical & Dental College, 2019)
Introduction: Urinary incontinence (UI) is a common, debilitating and costly problem in women. This problem has detrimental eﬀects on health related quality of life. UI does not lead to death, but it causes substantial debility, social seclusion, psychologic stress and economic burden. Objectives: to determine the frequency of diﬀerent factors of urinary incontinence in females. Methodology: A total of 85 women with urinary incontinence of age 25-65 years were included. Patients with taking immunosuppressive medicines, h/o pelvic trauma and spinal cord injury were excluded. After taking informed written consent and relevant history, all risk factors were noted in each patient.. Results: In my study, the risk factors associated with urinary incontinence in females include age >45 years (48.24%), parity >3 (47.06%), obesity (89.41%), vaginal delivery (71.76%), post hysterectomy (28.24%), episiotomy (48.24%), weight of baby>4 kg (50.59%), menopause (25.88%), smoking (32.94%), diabetes mellitus (21.18%) and urinary tract infection (61.18%). Conclusion: This study concluded that early screening and management of these factors should be done in every woman with urinary incontinence to prevent this devastating condition and improving the social life of these particular patients.